2018
DOI: 10.1111/clr.13123
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term biological complications of dental implants placed either in pristine or in augmented sites: A systematic review and meta‐analysis

Abstract: Aim:To investigate and compare the prevalence of biological complications and failure of implants placed in pristine vs. augmented sites after a mean observation period of at least 10 years. Materials and methods:The focused question "In patients with osseointegrated dental implants, are there differences in biological complications and implant failure at implants placed in pristine vs. augmented sites?" was addressed using the Population, Exposure, Comparison and Outcome criteria. Electronic and manual search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 74 publications
2
46
0
2
Order By: Relevance
“…The aggregated mean implant survival rate ( n studies = 27) was comparable to previous studies reporting implants placed in pristine sites (Pjetursson, Asgeirsson, Zwahlen, & Sailer, ; Pjetursson, Thoma, Jung, Zwahlen, & Zembic, ; Salvi et al., ). However, bone level changes were seldom reported ( n studies = 9).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The aggregated mean implant survival rate ( n studies = 27) was comparable to previous studies reporting implants placed in pristine sites (Pjetursson, Asgeirsson, Zwahlen, & Sailer, ; Pjetursson, Thoma, Jung, Zwahlen, & Zembic, ; Salvi et al., ). However, bone level changes were seldom reported ( n studies = 9).…”
Section: Discussionsupporting
confidence: 83%
“…Due to the associated comorbidities of augmentation procedures, such as post‐operative infections, wound dehiscences or neurosensory disorders, other approaches besides VRA have been proposed (e.g., short dental implants). These therapeutic modalities have proven to be effective and valid alternative treatments to sinus floor elevation or VRA, with reduced morbidity and high patient satisfaction (Hammerle & Jung, ; Nisand, Picard, & Rocchietta, ; Salvi, Monje, & Tomasi, ; Thoma, Haas, et al., ; Thoma, Zeltner, Husler, Hammerle, & Jung, ). However, in cases with limited bone availability for placing short implants, or due to restorative considerations, VRA may be the best therapy choice as it offers an opportunity for augmenting lost bony structure and often leads to improved aesthetic outcomes (Salvi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…DBBM has a slow bio‐absorbability and presents with the most extensive documentation among biomaterials used in augmentation procedures in implant dentistry (Haugen, Lyngstadaas, Rossi, & Perale, ; Sanz et al, ). The question whether there are differences in the occurrence of peri‐implantitis or other biological complications around implants placed in augmented or pristine bone sites was addressed in a systematic review by Salvi, Monje, and Tomasi (). It was reported that the included studies presented with a high variability regarding patient selection, eligibility criteria, and case definitions of peri‐implantitis.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the included studies presented with a high variability regarding patient selection, eligibility criteria, and case definitions of peri‐implantitis. Although the meta‐analysis by Salvi et al () failed to disclose differences in the occurrence of biological complications between pristine and augmented bone sites, it was concluded that implants placed in augmented bone exhibited higher variability and lower predictability concerning peri‐implantitis than implants placed in pristine bone. Considering the challenges in performing clinical studies with appropriate study design and patient selection as pointed out by Salvi et al (), the question on potential differences between augmented and pristine bone sites regarding peri‐implantitis may also be addressed in pre‐clinical in vivo trials.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term biological complications of dental implants placed either in pristine or in augmented sites: A systematic review and metaanalysis (Salvi, Monje, Tomasi, 2018).…”
Section: Introductionmentioning
confidence: 99%